2018
DOI: 10.17305/bjbms.2018.3565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epinephrine on heart rate variability and cytokines in a rat sepsis model

Abstract: Catecholamines have both anti-inflammatory and vasoactive properties. A decreased cardiac response to catecholamines has been associated with a high risk of death in sepsis and septic shock. The aim of this study was to investigate the effects of epinephrine (EPI) on heart rate variability and autonomic balance, as well as cytokine levels, in a rat sepsis model. Thirty-six male Sprague-Dawley rats were assigned to 4 experimental groups and 2 control groups of 6 rats each. The rats in the experimental groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…The incidence of bloodstream infection in the VLBW cohort in this study was 15%, lower than what was previously reported (21%) by the NICHD Neonatal Research Network; however, other sites of infection were identified in our study cohort. The mortality rate was higher than that reported in the literature, 19.4% compared to 10% 3 . This finding reflects the risk of a referral population, referred for surgical issues, and the known risks for community-born VLBW infants [21][22][23][24].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The incidence of bloodstream infection in the VLBW cohort in this study was 15%, lower than what was previously reported (21%) by the NICHD Neonatal Research Network; however, other sites of infection were identified in our study cohort. The mortality rate was higher than that reported in the literature, 19.4% compared to 10% 3 . This finding reflects the risk of a referral population, referred for surgical issues, and the known risks for community-born VLBW infants [21][22][23][24].…”
Section: Discussioncontrasting
confidence: 66%
“…This might be due in part to the high prevalence of morbidities and procedures in our unit that elevate HRC scores thus limiting their utility. In addition, HRC is known to vary with factors such as age, gender, medications, and mechanical ventilation [17][18][19][20]. Nevertheless, a tighter protocol regarding the action towards patients with increasing scores might clarify the utility of HRC monitoring in early identification of infections in our NICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since younger patients tend to have higher HRV ( 6 , 19 ), we tried to mitigate this effect by normalizing HRC to a patient’s median HR, which is expected to be higher in younger patients. Future larger, prospective studies should match for age or use multivariable regression analyses to adjust for age and other potential confounders (e.g., sedatives, vasoactive medications, mechanical ventilation, cardiac dysfunction) ( 20 , 21 ). Finally, due to the retrospective nature of this study, we were not able to assess the ability of HRC to predict BD, which would require HR measurements collected and BD testing performed prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive catecholamine hormones can increase the energy consumption of cardiomyocytes, increase the metabolic burden of myocardial microcirculation, enhance the oxidative stress levels of cardiomyocytes, and affect the myocardial rhythm. The compensatory work of the heart and inadequate coronary blood perfusion accelerate the imbalance in myocardial oxygen supply and demand 105–108 …”
Section: Main Bodymentioning
confidence: 99%
“…The compensatory work of the heart and inadequate coronary blood perfusion accelerate the imbalance in myocardial oxygen supply and demand. 105 , 106 , 107 , 108 …”
Section: Main Bodymentioning
confidence: 99%